Quality of life and sexual function of women operated on reproductive system organs - Lashkul О. S. (Zaporozhye Medical Journal, 2018)
Aim – to study the effect of planned gynecological operations on the integral characteristics of physical, psychological, emotional, social and sexual functioning of women. Materials and methods. Quality of life and sexual function were studied in 165 patients who underwent planned gynecological operations. Depending on the type of surgical treatment patients were divided into 6 groups: the 1st group – 20 patients (vaginal hysterectomy without FTS), the 2nd group – 23 patients (abdominal hysterectomy without FTS), the 3rd group – 54 patients (laparoscopic operations on the uterine appendages without FTS), the 4th group – 21 patients (vaginal hysterectomy with FTS), the 5th group – 20 patients (abdominal hysterectomy with FTS), the 6th group – 27 patients (laparoscopic operations on the uterine appendages with FTS). To assess the quality of life a short version of the SF-36 questionnaire was used. The questionnaire was developed at the US Institute of Health, author J. E. Ware, and contains 36 items. They are grouped so that they reflect 8 different aspects related to health. The results for each scale are presented in a point scale (from 1 to 100), where a higher score corresponds to a better quality of life. To assess the sexual function a questionnaire was conducted using the female sexual function index (FSFI). The questionnaire includes 19 items that provide of characteristics of desire, excitement, lubrication, orgasm, getting sexual satisfaction and dyspareunia presence assessment. The minimum score is 2, the maximum is 36. Stages of the questionnaire: before the operation and three months after the operation. Results. In patients before and after laparoscopic surgery on uterine appendages without FTS and with FTS, the mean values of the female sexual function index were significantly higher after surgery and reached the maximum value of 36. So, by questionnaire before and after 3 months it has been found that the indicators characterizing the quality of life (physical and vital activity, social and role functioning, emotional and mental health) in patients of all groups significantly improved, so the final result of surgical interventions was achieved. A significant contribution to the health physical component overall index was made by the index of pain intensity (BP), which in all groups increased by 2–3 times in comparison with the corresponding preoperative values. When comparing the similar operations with FTS and without FTS, it has been revealed that 3 months after vaginal hysterectomies and operations on the uterine appendages the health physical component total index was significantly higher in groups with FTS. In the group of patients who underwent abdominal hysterectomy, the physical component of health total score did not change significantly, whereas the psychological component of health total index increased significantly in patients who had been treated with a multimodal approach for maintaining the postoperative period. Sexual function in women 3 months after abdominal hysterectomy (FTS) and laparoscopic operations on the uterine appendages with FTS and without FTS increased significantly. There were no significant differences in FSFI in women who underwent vaginal hysterectomy. This fact can be explained by the age of patients who were in menopause. Conclusions. Indicators of physical and mental health components improved in patients of all groups three months after surgery. In patients operated by using the multimodal FTS strategy the most significant increase of health physical component was identified in the group of vaginal hysterectomy three months after the operation. There were no significant differences in the sexual function of women in the long-term postoperative period after vaginal hysterectomies. After abdominal hysterectomy with FTS a significant improvement of the female sexual function index was observed by 27.2 %. After operations on the uterine appendages without FTS and with FTS the index of female sexual function increased on average by 11.6 % and 12.8 %, respectively.